Critical success factors for Lean implementation in IT outsourcing relationships: A multiple case study. Issue 3 (3rd June 2019) - Blijleven, Vincent; Gong, Yiwei; Mehrsai, Afshin; Koelemeijer, Kitty
Abstract : Purpose: Following positive results of Lean implementation in manufacturing environments, Lean has become an emerging philosophy for clients and suppliers of information technology (IT) services. However, how to implement Lean in IT outsourcing relationships has been addressed sparsely in academic literature. The purpose of this paper is to investigate critical success factors (CSFs) for implementing Lean in IT outsourcing relationships. Key findings, implications and avenues for future research are discussed. Design/methodology/approach: Six IT outsourcing relationships were qualitatively investigated by means of 36 semi-structured interviews. CSFs were identified based on interview transcription analyses, selection techniques and expert reviews. Findings: In total, 16 CSFs for Lean implementation in IT outsourcing relationships are identified and described. Practical implications: The CSFs presented in this paper indicate key areas that deserve managerial attention to steer Lean implementation efforts in IT outsourcing relationships in a favorable direction. Originality/value: This study is the first to describe the phenomenon of "Lean IT outsourcing" and provides researchers and practitioners with a foundation to further examine Lean implementation in IT outsourcing relationships.